"Self-Medication with Cannabis" (Ricos Biology, 2025)
Self-medication utilizing cannabis has collected meaningful attention on account of its perceived healing benefits and developing permissible frameworks. Individuals repeatedly count on cannabis for directing incessant pain, tension, depression, and additional healing conditions, frequently outside adequate counseling from healthcare providers. This practice raises detracting questions about security, efficacy, and the potential for misuse. Although cannabinoids like THC and CBD have proved promise in considering certain environments, discrepancies in product features, drug, and individual reactions present challenges in ensuring optimum effects.This review explores the patterns, ambitions, and risks that guide self-cure using marijuana. Key determinants influencing self-cure contain accessibility, socioeconomic rank, and unhappiness accompanying conventional situations. The impact of authorization on self-medication currents and the populace most affected by marijuana procedures is emphasized. Despite anecdotal evidence upholding allure therapeutic use, strong dispassionate tests are necessary to confirm these claims and address concerns about reliance, cognitive deterioration, and drug interplays.Ethical considerations stand when things use marijuana as a substitute for recommended healing treatments. Public health concerns, containing the normalization of marijuana use and its potential social belongings, are explained in light of changeful public ideas. This review underscores the need for evidence-based directions to guide things self-medicating with marijuana and the healthcare artists advising bureaucracy.